2015
DOI: 10.1149/06801.1045ecst
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of LSCF Cathode Induced by SO2 in Air

Abstract: Sulfur dioxide (SO 2 ) is one of the major impurities in air and it induces performance degradation of SOFC cathodes. Our group has investigated the degradation behavior of (LaSr)(CoFe)O 3 (LSCF) cathodes by sulfur dioxide (SO 2 ) containing air. It is clearly observed that SO 2 -induced degradation is affected by cell operation conditions, such as impurity concentration and the operating temperature. We observed two degradation steps; one is a rapid degradation rate occurring at an early stage and the other i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Relationship between the R ohmic and R p for the LSCF6428 cathode under 1 ppm SO 2 degradation, which is previously reported in ECS transaction. 16 The data for 0.1 ppm at 1073 K, which is previously reported, 14 is also plotted. Inset: R ohmic and R p .…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Relationship between the R ohmic and R p for the LSCF6428 cathode under 1 ppm SO 2 degradation, which is previously reported in ECS transaction. 16 The data for 0.1 ppm at 1073 K, which is previously reported, 14 is also plotted. Inset: R ohmic and R p .…”
Section: Resultsmentioning
confidence: 80%
“…For the degradation recovery test, LSCF6428 was first exposed to 1 ppm SO 2 for 3 h at operating temperature of either 923 K or 973 K, and the Time dependence of the rate of decrease in current under potentiostatic condition (−0.2 V vs. RE(air)) at each temperature, which is previously reported in ECS transaction. 16 The data for 0.1 ppm at 1073 K, which is previously reported, 14 is also plotted.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…In particular, for the sulfur poisoning of active cathodes, it becomes more difficult to identify whether sulfur poisoning appears or not even when detailed analyses on sulfur accumulation on cathode will be available with SIMS etc. This is because the degradation rate in cathode is not linearly proportional to the amount of sulfur accumulated in cathodes; significant degradations may occur even due to an extremely small amount of sulfur particularly at low temperatures . In such a case, the observed slope in correlation may help in considering possible sources of degradations, since similar correlations were obtained for sulfur poisoning in button cell experiments.…”
Section: Correlation Between Cathode Overpotential and Ohmic Lossmentioning
confidence: 85%
“…[6][7][8][9][10] In addition to Cr species, sulfur, most likely from the air stream, can deposit at the cathode side, poisoning and degrading the cell performance. [11][12][13][14][15][16][17] La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ (LSCF) perovskite material has been extensively studied and regarded as one of the most promising cathode candidates for IT-SOFCs due to its high mixed electronic and ionic conductivities and high catalytic activity for the O 2 reduction reaction. [18][19][20] However, despite the promising potential of the LSCF material as the IT-SOFC cathode, few studies have been reported on the interaction between the LSCF electrode and sulfur dioxide and there are significant discrepancies in the mechanism of the sulfur deposition and poisoning for the O 2 reduction reaction at the LSCF cathode.…”
mentioning
confidence: 99%